Instrumentos endodonticos de níquel-titânio : análise de defeitos antes e após o uso através da microscopia eletrônica de varredura - Laurindo, Flávia Villela (2015)
Technically all steps are crucial to obtain excellence in required endodontic treatment. To minimize accidents during the preparation chemical and mechanical changes in the methods and instrumentation in nickel titanium endodontic instruments has been suggested. New instruments are often launched on the market without proper knowledge of their properties and limitations, therefore, the purpose of this thesis was to evaluate the defects in surfaces of instruments reciprocantes Unicone and Prodesign, comparing them to the instruments of continuous rotation Prodesign S and Wizard Navigator. Each system was used three times in simulated root canals and the surfaces of instruments were analyzed by scanning electron microscopy. After statistical analysis of the results, it was concluded that the instruments reciprocantes Prodesign and Unicone presented a progressive increase of surface defects, suggesting that single use for increased security during the treatment. The instruments of continuous rotation Wizard Navigator and Prodesign S presented smaller defects after the third use in relation to flute deformation, but with a trend to enhance material loss. In addition, a review of the literature was performed to cover the findings of recent years on reciprocal and continuous systems.